2016
DOI: 10.1093/aob/mcw113
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical rhizosphere processes affecting root water uptake

Abstract: Despite detailed images of water content, water fluxes and soil structure in the rhizosphere, a general understanding of how the rhizosphere affects root water uptake is still lacking. The missing elements of the puzzle are the gradient in water potential around roots. Measurements of the xylem water potential at varying soil water potentials and transpiration rates supported by numerical models of root water uptake would allow the estimation of the water potential across the rhizosphere. Such measurements are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 57 publications
4
62
0
3
Order By: Relevance
“…Important advances in imaging techniques make it possible to obtain high resolution images for the much necessary quantification of the physical soil structure around the roots (Carminati et al, 2016;Hinsinger et al, 2009). These images have shown that compared to the bulk soil, the rhizosphere exerts a considerable heterogeneity driven by the propagation of mucilage within the pore space, changes in soil structure around roots (e.g., by soil swelling and shrinkage), the emergence of water repellent zones, the formation of rhizosheath and physical interactions with microorganisms (Carminati et al, 2016). Spatial variability in root-soil contact (partial contact) may further add to this complexity (Carminati et al, 2013;de Willigen et al, 2018;Herkelrath et al, 1977;North & Nobel, 1997;Veen et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Important advances in imaging techniques make it possible to obtain high resolution images for the much necessary quantification of the physical soil structure around the roots (Carminati et al, 2016;Hinsinger et al, 2009). These images have shown that compared to the bulk soil, the rhizosphere exerts a considerable heterogeneity driven by the propagation of mucilage within the pore space, changes in soil structure around roots (e.g., by soil swelling and shrinkage), the emergence of water repellent zones, the formation of rhizosheath and physical interactions with microorganisms (Carminati et al, 2016). Spatial variability in root-soil contact (partial contact) may further add to this complexity (Carminati et al, 2013;de Willigen et al, 2018;Herkelrath et al, 1977;North & Nobel, 1997;Veen et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, root water uptake can be well approximated by a single pathway and by using an average root hydraulic conductivity (Landsberg & Fowkes, ; Zarebanadkouki et al, ). Water flow in the root can thus be described by the following equation (Carminati et al, ; Couvreur et al, ; Javaux et al, ) qroot=Kroot)(hroothxylem where qroot (cm/s) is the root water uptake rate, Kroot (cm/s) is the overall hydraulic conductivity of the root tissue between the root surface and the xylem, hroot (cm) is the pressure at the root surface, and hxylem (cm) is the xylem pressure. Since the fundamental work of Gardner (), an extensive range of studies simulated the water flow from the bulk soil to the root in terms of a cylindrical geometry.…”
Section: Theoretical Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even with such an acceleration of research, the specific distribution and paths that the fluid takes from the soil matrix into and through the plant itself remain unknown . As stated by Carminati et al (2016), "Coupling these measurements with imaging techniques that allow visualization of the root architecture and the structure and moisture of the rhizosphere could be the ultimate experiment to measure the rhizosphere properties." The analysis presented here clearly indicates the effectiveness of combining 2-D tank systems with imaging techniques such as LTM to furthering understanding of high spatial and temporal fluid distribution and moisture gradients in the rhizosphere directly under the influence of plant roots.…”
Section: Imaging Capabilitiesmentioning
confidence: 99%
“…This is a crucial knowledge gap in terms of the biogeochemical influences on the hydrologic processes occurring in the rhizosphere, as stated by Bengough (2012), particularly the effect that root exudates have on the nonequilibrium dynamics of interfaces and flow in porous media. Carminati et al (2016) recently analyzed the rhizosphere processes to more thoroughly elucidate the system, with a particular focus on determining the role of mucilage in root water uptake. They found that wet mucilage enhances fluid transport, but when dry, the mucilage causes hydrophobic tendencies in the rhizosphere .…”
Section: Introductionmentioning
confidence: 99%